Model Spasial Dan Faktor Pengontrol Akuifer Airtanah Dangkal Untuk Penentuan Zona Konservasi Air Tanah Di Kelurahan Oebufu Kota Kupang - Karels, Dolly Willy (Fakultas Teknik, Universitas Brawijaya, 2014)
The Oebufu Village geologically composed of limestones that hydrological growing in this area should be karst hydrology, but at this location, shallow groundwater are found in dig well at 5.63 m to 25.26 m depth, that are not commonly found in karst area. Therefore, the study aims to determine the spatial model of shallow groundwater in the study area and its controlling factors. Geoelectric equipment used to determine the presence of aquifer, IPI2WIN and RES2DINV software used to analyze the results of geoelectric, while the Surfer software used to create the shallow groundwater aquifer spatial model. The results of the study provide the output of the spatial model of shallow groundwater; controlling factors of the shallow groundwater are: (a) lithology, a soluble form of limestone and formed the secondary porosity; (b) the rock exposed, exposed rock thickness determines the depth of the aquifer; (c) hydrological system, is different hydrological system between the back and the foothills; and groundwater conservation zones covering the entire study site. Making watertight septic tank to accommodate domestic waste is a groundwater pollution control efforts in Oebufu Village, that its geological formation were limestone.Key word: Spatial model, controlling factor, shallow groundwater, conservation zone, Oebufu Village